Evaluation of disaster preparedness for mass casualty incidents in private hospitals in Central Saudi Arabia - Shalhoub, Abdullah A. Bin (Saudi Med J, 2017)
OBJECTIVES: To identify and describe the hospital disaster preparedness (HDP) in major private hospitals in Riyadh, Saudi Arabia. METHODS: This is an observational cross-sectional survey study performed in Riyadh city, Saudi Arabia between December 2015 and April 2016. Thirteen major private hospitals in Riyadh with more than 100 beds capacity were included in this investigation. RESULTS: The 13 hospitals had HDP plan and reported to have an HDP committee. In 12 (92.3%) hospitals, the HDP covered both internal and external disasters and HDP was available in every department of the hospital. There were agreements with other hospitals to accept patients during disasters in 9 facilities (69.2%) while 4 (30.8%) did not have such agreement. None of the hospitals conducted any unannounced exercises in previous year. CONCLUSION: Most of the weaknesses were apparent particularly in the education, training and monitoring of the hospital staff to the preparedness for disaster emergency occasion. Few hospitals had conducted an exercise with casualties, few had drilled evacuation of staff and patients in the last 12 months, and none had any unannounced exercise in the last year.